Prioritizing BIM applications and advantages in construction project management - Farzad Fani; Roohollah Taherkhani; Majid Sabzehparvar (مهندسی و مدیریت ساخت)
Managers and employers in the construction industry should become more familiar with Building Information Modeling (BIM) and its applications as a tool for successful project management. Research and surveys conducted in other countries indicate a growing trend among construction industry stakeholders to use BIM in recent years, and this trend continues to rise. In this study, after identifying the applications of BIM through literature review, case studies, and articles, a group of experts and specialists in areas related to BIM workflows were surveyed using the Delphi technique about the impact and benefits of BIM applications on four project management criteria: cost, time, quality, and scope (which according to the PMBOK standard, are the four basic knowledge areas of project management). Fuzzy TOPSIS technique is utilized for prioritizing BIM applications based on their potential impact on projects. Ultimately, identifying the most important and impactful applications for implementation planning is possible